Dampak Makanan Cepat Saji Bagi Kesehatan Tubuh Pada Kalangan Remaja - Anggie Annisa Permatasari; Fransisca Putri Ardita; Agista Putri Prasetya; Nurul Anggraini; Siti Marpuah; Erintya Asanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
This counseling focuses on the lack of awareness among teenagers about their body health, where up to now teenagers still seem to be indifferent to their body health. This is because teenagers now tend to prefer consuming fast food over healthy food. The aim of this counseling is to make teenagers aware of efforts to maintain body health by reducing consumption of fast food and to find out the reasons why teenagers don't like healthy food and are reluctant to consume it. This counseling was carried out because it was motivated by teenagers who tend to prefer consuming fast food compared to vegetables or other healthy foods. This extension uses quantitative methods by measuring the extent to which they understand about fast food and healthy food to find the necessary data. From the results found in the field, some teenagers prefer to consume fast food compared to healthy food. An obstacle to implementing a healthy lifestyle is that teenagers tend to prefer flavored foods or drinks rather than foods such as vegetables or water. So we as health promoters must be able to provide motivation, support and examples for teenagers to eat healthy food and adopt a healthy lifestyle.